Healing logics : culture and medicine in modern health belief systems - Brady, Erika, 1952- (Logan, Utah : Utah State University Press, 2001)
"Scholars in folklore and anthropology are more directly involved in various aspects of medicine--such as medical education, clinical pastoral care, and negotiation of transcultural issues--than ever before. Old models of investigation that artificially isolated "folk medicine," "complementary and alternative medicine," and "biomedicine" as mutually exclusive have proven too limited in exploring the real-life complexities of health belief systems as they observably exist and are applied by contemporary Americans. Recent research strongly suggests that individuals construct their health belief systmes from diverse sources of authority, including community and ethnic tradition, education, spiritual beliefs, personal experience, the influence of popular media, and perception of the goals and means of formal medicine. Healing Logics explores the diversity of these belief systems and how they interact--in competing, conflicting, and sometimes remarkably congruent ways. This book contains essays by leading scholars in the field and a comprehensive bibliography of folklore and medicine."--Publisher's description
Understanding folk medicine / Bonnie B. O'Connor and David J. Hufford -- Invisible hospitals : botánicas in ethnic health care / Michael Owen Jones and Patrick A. Polk, with Ysamur Flores-Peña and Roberta J. Evanchuk -- Poor Man's Medicine Bag : the empirical folk remedies of Tillman Waggoner / Richard Blaustein, Anthony Cavender, and Jackie Sluder, with comments by Tillman Waggoner -- Integrating personal health belief systems : patient-practitioner communication / Shelley R. Adler -- Competing logics and the construction of risk / Diane E. Goldstein -- New age sweat lodge / William M. Clements -- Evergreen : the enduring voice of a nine-hundred-year-old healer / Frances M. Malpezzi -- Reflections on the experience of healing : whose logic? Whose experience? / Bonnie Glass-Coffin -- Hózhó factor : the logic of Navajo healing / Barre Toelken -- Bibliography of folklore and medicine / Michael Owen Jones and Erika Brady, with Jacob Owen and Cara Hoglund.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Traditional medicine; Healing; Medical anthropology; Ethnology; Cross-cultural studies; Mental healing; Communication in medicine; Alternative medicine; Therapeutics, Physiological; Medicine, Traditional; Anthropology, Cultural; Complementary Therapies; Cross-Cultural Comparison; Mental Healing; Recovery of Function; Anthropology, Medical; Ethnology; Médecine populaire; Guérison.; Anthropologie médicale.; Communication en médecine.; Ethnologie; Médecines parallèles.; Études transculturelles; Guérison par l'esprit.; traditional medicine; ethnology; social anthropology; SOCIAL SCIENCE -- Folklore & Mythology; SOCIAL SCIENCE -- General; Therapeutics, Physiological; Mental healing; Ethnology; Cross-cultural studies; Communication in medicine; Alternative medicine; Healing; Medical anthropology; Traditional medicine; Volksgeneeskunde; Genezing; Medische antropologie